IMPLEMENTASI PERATURAN DAERAH NOMOR 28 TAHUN 2011 TENTANG PAJAK REKLAME DI KABUPATEN HULU SUNGAI UTARA - Irza Setiawan (stiatabalong.ac.id, 2019)
In Hulu Sungai Utara Regency, the issue of billboards is regulated in the Hulu Sungai Utara district regulation Number 28 of 2011 concerning advertisement tax, the related Office related to the implementation of this regional regulation is the Investment Office, One Stop Integrated Services and Labor, licensing, Agency Management of Regional Taxes and Retributions related to advertisement tax, the Civil Service Police Unit as supervisor, and the City Planning Division as structuring the beauty of the city at the Housing, Settlements and Environment Agency, as a disposition to place billboards. The implementation of this advertisement tax still found problems such as the discovery of billboards with three layers of banners, as well as the installation of banners in the prohibition zone. The results of the research indicate that the communication of the relevant institutions already understands their respective main tasks and functions in implementing Regional Regulation number 28 of 2011 concerning Billboard Taxes, only the lack of communication between institutions, so that the process of implementing Regional Regulations relating to communication has not well, the resources responsible for installing billboards are not yet available, while if referring to the duties and functions of the Regional Tax and Retribution Management Agency it is not clearly regulated who is responsible for carrying out the billboard installation, and if it is associated with Regional Regulation No. 28/2011 not regulated by officers or special resources in carrying out the installation of this billboard, Keywords: implementation; policy; local regulation.